Clinical utility of OCTA (Canadian Eye Care Today, 2022)
Optical coherence tomography angiography (OCTA) is a novel technology that can produce images of blood flow with unprecedented resolution of all the vascular layers of the retina and choroid in a rapid, non-invasive fashion. The technology dates back to 2005, when researchers demonstrated that blood flow could be visualized using swept-source OCT (SS-OCT) based on properties of the Doppler signal. Since then, advancements have led to the technology becoming widely available for the clinical community, aiding in patient diagnosis and monitoring. This review article will highlight examples of ophthalmic diseases where OCTA has important clinical utility; specifically, diabetic retinopathy, age-related macular degeneration, retinal vein occlusions, white-dot syndromes, and early research into neurodegenerative diseases.